Performance of Broiler Chickens Offered Drinking Water Contained Water Extracted Beluntas (Pluchea indica L.) Leaf and Sugar Cane - A Sudarman; . Sumiati; R Kaniadewi (Media Peternakan, 2012)
Our previous study showed that the addition of water extracted beluntas leaf into drinking water could be used as an anti-stress and improved performance of broiler chicken. However, the addition was only up to 10% of drinking water. The objective of this experiment was to study whether the addition of sugar and water extracted beluntas leaf in levels higher than 10% of drinking water can give greater benefit on performances and meat cholesterol content of broiler. Two hundred sixteen DOCs CP707 strain were reared for four weeks in high stocking density of 15 birds/m2. The birds were subjected to experimental drinking waters with or without water extracted beluntas leaf (v/v) and sugar which is consisted of T1 (only drinking water), T2 (drinking water + commercial antistress), T3 (drinking water + 10% extract of beluntas leaf ), T4 (drinking water + 20% extract of beluntas leaf), T5 (drinking water + 40% extract of beluntas leaf), T6 (drinking water + 80% extract of beluntas leaf), T7 (drinking water + 40% extract of beluntas leaf + 1.6% sugar), and T8 (drinking water 80% extract of beluntas leaf + 3.1% sugar). The results showed that water extracted beluntas leaf addition higher than 10% significantly reduced (P < 0.05) body weight gain, final body weight, and increased (P < 0.05) feed conversion ratio. It is concluded that the addition of water extracted beluntas leaf more than 10% into drinking water cannot give greater benefit on performances as an antistress of broiler. Sugar addition cannot help the disadvantage due to the bitter taste of higher level of water extracted beluntas leaf addition.